1962
DOI: 10.1039/tf9625800923
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction from halide solutions. Part 3.—Dissociation in the organic phase

Abstract: A study of the influence of the metal concentration on the extraction of iron and gold from hydrochloric acid solutions indicates that the extracting acid, HMCL, dissociates in the organic phase at high dilution. This conclusion is substantiated by the effect of the hydrochloric acid concentration on the extraction of gold from solutions containing trace concentrations and by the influence of strong acids on the extraction from such systems. A direct demonstration of the dissociation by migration experiments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The interpretation was confirmed by osmometric measurements. Maddock et al (19) report the dissociation of HAuCl 4 in various organic phases, as shown by distribution measurements and confirmed by migration experiments.…”
Section: Discussionmentioning
confidence: 81%
“…The interpretation was confirmed by osmometric measurements. Maddock et al (19) report the dissociation of HAuCl 4 in various organic phases, as shown by distribution measurements and confirmed by migration experiments.…”
Section: Discussionmentioning
confidence: 81%
“…The lower MC1 3 , or higher MCI 2or MC\l~ species, despite their known presence in many cases in the aqueous solutions, have generally not been identified in the organic extract. On the other hand, it was necessary to assume the existence of complexes other than MC1± in order to fit distribution data into sets of mass-action law equations/ 208,221) The extractability of bivalent metal halides (223,224) has not been markedly improved, even using butanol as solvent. On the other hand, it was necessary to assume the existence of complexes other than MC1± in order to fit distribution data into sets of mass-action law equations/ 208,221) The extractability of bivalent metal halides (223,224) has not been markedly improved, even using butanol as solvent.…”
Section: Metal Extractionmentioning
confidence: 99%